Cross-Strait Economic Relations: Recent Development and Implications for Taiwan - Min-Hua Chiang; Bernard Gerbier (Revue de la Régulation)
This article purports to elucidate the recent progress of the Cross-Strait economic relations and the implications for Taiwan’s economy and its political sovereignty. There are three points made in this article. First, over the last decade, Taiwan’s investment in China has changed from labour intensive manufacturing made mostly by small and medium companies to high technology led by large enterprises. Although Taiwanese firms benefitted from enlarging its economies of scale, the overdependence on manufacturing production in China has resulted in Taiwan’s de-industrialization. Second, Taiwan’s trade has been increasingly dependent on China rather than vice-versa. Even though the conditions for the political reconciliation are still not mature at present, Taiwan’s relatively stronger economic dependence on China will put it in a disadvantageous position in the future negotiation. Third, in view of the intensified economic integration with China, the signing of Economic Cooperation Framework Agreement is unavoidable. However, Taiwan’s minimal involvement in the economic integration with other regional economies will push it to open more to China as it offers the easiest short-term solution to Taiwan’s lack of internal dynamics for economic growth. Cross-Strait economic integration for China is also encouraging as it will facilitate its “peaceful rise” policy as well as serve its long term political goal for Taiwan.